Interactive roles of fire seasons and biological invasions in the short-term dynamics of tropical savannas - Dezotti, Gabriela [UNESP]; Fidelis, Alessandra [UNESP]; Damasceno, Gabriella [UNESP]; Siqueira, Tadeu [UNESP] (Wiley, 2024)
Aim: Changes in fire regimes and biological invasions are major threats to tropical savannas. Fire is a key driver of community composition in these ecosystems and can be used as a management tool to control some invasive alien species, while being advantageous to native ones. However, we still do not fully comprehend the interactive effects of these threats on native plant communities. Here, we conducted an experiment in southeastern Brazil to investigate how variation in the composition of native communities invaded either by Melinis minutiflora or Urochloa brizantha is affected by fire in different seasons: early-dry season, mid-dry season and late-dry season in comparison to fire suppression. Location: Itirapina, state of São Paulo, southeastern Brazil (22°14′07″S 47°53′07″W). Results: The effects of fire seasons and invasive species were independent for species richness but interactive for species gains and losses. In general, the identity of the invasive species was a key factor driving community dynamics, with fire seasons playing a weaker role. Invaded communities changed gradually over time and the major changes happened over longer time lags. Communities invaded by M. minutiflora gained more species than those invaded by U. brizantha. Thus, communities invaded by M. minutiflora also had more variation in their species richness through time than those invaded by U. brizantha. Conclusions: Although biological invasions and fire seasons interacted as drivers of change in native savanna communities, the identity of the invasive species played a stronger role. Communities invaded by M. minutiflora gained more species and were more variable than those invaded by U. brizantha.
Keywords: Brazilian savannas; campo sujo; community dynamics; diversity partitioning; Melinis minutiflora; prescribed fires; tropical savannas; Urochloa brizantha